2018
DOI: 10.1088/1748-9326/aa9e94
|View full text |Cite
|
Sign up to set email alerts
|

Changing response of the North Atlantic/European winter climate to the 11 year solar cycle

Abstract: Recent studies have presented conflicting results regarding the 11 year solar cycle (SC) influences on winter climate over the North Atlantic/European region. Analyses of only the most recent decades suggest a synchronized North Atlantic Oscillation (NAO)-like response pattern to the SC. Analyses of long-term climate data sets dating back to the late 19th century, however, suggest a mean sea level pressure (mslp) response that lags the SC by 2-4 years in the southern node of the NAO (i.e. Azores region). To un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…As noted in Figure , the significant in‐phase correlation between the SC and southern China precipitation only exists in late winter, while in early winter, these correlations are nonsignificantly anticorrelated. This change is consistent with the evident subseasonal variations in SC signals in NAE circulation anomalies identified by recent studies (Gray et al, ; Ma et al, ). In late winter, the circulation response features a significant negative pressure anomaly over the Iceland region that is approximately synchronous to the SC, which reflects a direct top‐down influence from the stratosphere via heating effects of the solar ultraviolet irradiance (Chen et al, ; Ineson et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As noted in Figure , the significant in‐phase correlation between the SC and southern China precipitation only exists in late winter, while in early winter, these correlations are nonsignificantly anticorrelated. This change is consistent with the evident subseasonal variations in SC signals in NAE circulation anomalies identified by recent studies (Gray et al, ; Ma et al, ). In late winter, the circulation response features a significant negative pressure anomaly over the Iceland region that is approximately synchronous to the SC, which reflects a direct top‐down influence from the stratosphere via heating effects of the solar ultraviolet irradiance (Chen et al, ; Ineson et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…The extended memory of the ocean heat‐content anomalies and their feedbacks onto the atmosphere induce a lagged solar influence on the Azores mean sea level pressure (Andrews et al, ; Gray et al, ; Scaife et al, ). In the NAE region, the direct top‐down solar forcing and solar‐induced ocean‐atmosphere coupling are dominant during different winter phases, thus producing very different surface climate impacts between early and late winter (Gray et al, ; Ma et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In our simulations, longwave and especially shortwave forcing induce a clear lagged positive phase of the NAO and the NAM (Figure ), with cooling in the western North Atlantic/Greenland area and warming over much of European Russia, northern, and eastern Asia (though results are sensitive to the choice of lag time). Analyses of recent observations suggest a detectable influence of solar variability on the NAM (Frame & Gray, ; Gray et al, ), with the strongest positive SLP anomaly over the Azores with a lag of 2–4 years (Ma et al, ). This result is similar to that seen in our shortwave‐forced simulations but does not occur in our simulations forced by all wavelengths (either in December–February or in late winter, February–March).…”
Section: Resultsmentioning
confidence: 99%
“…This is also in accordance with Ma et al . () who show that after the 1940s the lagged response in the Azores is mainly observed in lag 2 years. However, with the current study we cannot rule out the possibility that in earlier times longer lags have also been important.…”
Section: Lagged Sunspot Activity Response In Slp and Umentioning
confidence: 98%
“…These patterns are not visible in Figure 5 because calculating zonal means averages out the opposite signals in the same latitudinal band. Ma et al (2018) have shown that the lagged response to sunspot activity in the Azores is sometimes significant even with lags 3 and 4 years when a very long time period since the mid-eighteenth century is considered. We also tested if adding longer lags to SA (3 and 4 years) would show up significant responses in our considered time period (not shown).…”
Section: Lagged Sunspot Activity Response In Slp and Umentioning
confidence: 99%